Targeting TRIM54/Axin1/β-Catenin Axis Prohibits Proliferation and Metastasis in Hepatocellular Carcinoma - Zhu, Jinrong; Wu, Yongqi; Lao, Shaoxi; Shen, Jianfei; Yu, Yijian; Fang, Chunqiang; Zhang, Na; Li, Yan; Zhang, Rongxin (Frontiers in Oncology, 2021)
Accumulating evidence demonstrates that dysregulation of ubiquitin-mediated degradation of oncogene or suppressors play important role in several diseases. However, the function and molecular mechanisms of ubiquitin ligases underlying hepatocellular carcinoma (HCC) remain elusive. In the current study we show that overexpression of TRIM54 was associated with HCC progression. TRIM54 overexpression facilitates proliferation and lung metastasis; however, inhibition of TRIM54 significantly suppressed HCC progression both in vitro and in vivo. Mechanically, we demonstrated that TRIM54 directly interacts with Axis inhibition proteins 1 (Axin1) and induces E3 ligase-dependent proteasomal turnover of Axin1, substantially induces sustained activation of wnt/β-catenin in HCC cell lines. Furthermore, we showed that inhibition of wnt/β-catenin signaling pathway via small molecule inhibitor significantly suppressed TRIM54-induces proliferation. Our data suggest that TRIM54 might function as an oncogenic gene and targeting TRIM54/Axin1/β-catenin axis signaling may be a promising prognostic factor and a valuable therapeutic target for HCC.